2013
DOI: 10.1158/2159-8290.cd-13-0108
|View full text |Cite
|
Sign up to set email alerts
|

A Hormone–DNA Repair Circuit Governs the Response to Genotoxic Insult

Abstract: Alterations in DNA repair promote tumor development, but the impact on tumor progression is poorly understood. Here, discovery of a biochemical circuit linking hormone signaling to DNA repair and therapeutic resistance is reported. Findings demonstrate that androgen receptor (AR) activity is induced by DNA damage, and promotes expression and activation of a gene expression program governing DNA repair. Subsequent investigation revealed that activated AR promotes resolution of double-strand breaks and resistanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
354
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(385 citation statements)
references
References 73 publications
26
354
5
Order By: Relevance
“…Moreover, DNA-PKc stabilizes the MYC oncoprotein (11) and physically interacts with EGFR, which is frequently overexpressed in epithelial human tumors. A recent study revealed a positive-feedback loop between DNA-PKc and the androgen receptor (AR) in prostate cancer cells, providing a rationale for targeting DNA-PKc in AR-driven malignancies, particularly in advanced prostate cancer (24). In contrast with these findings, decreased DNA-PKc activity and expression has been reported in ovarian cancers, where this loss of expression was associated with tumor progression and metastasis (12).…”
Section: Emerging Evidence For the Role Of Constitutive Dna Damage Inmentioning
confidence: 99%
“…Moreover, DNA-PKc stabilizes the MYC oncoprotein (11) and physically interacts with EGFR, which is frequently overexpressed in epithelial human tumors. A recent study revealed a positive-feedback loop between DNA-PKc and the androgen receptor (AR) in prostate cancer cells, providing a rationale for targeting DNA-PKc in AR-driven malignancies, particularly in advanced prostate cancer (24). In contrast with these findings, decreased DNA-PKc activity and expression has been reported in ovarian cancers, where this loss of expression was associated with tumor progression and metastasis (12).…”
Section: Emerging Evidence For the Role Of Constitutive Dna Damage Inmentioning
confidence: 99%
“…It was reported recently that DNA damage caused by ionizing radiation leads to the activation of AR, which in turn induces the expression of DNA repair genes that promote the survival of irradiated prostate cancer cells (47,48). Based on these reports, we expected that AR-inactivation would down regulate DDR signaling pathways and block the repair of damaged telomeres.…”
Section: Discussionmentioning
confidence: 94%
“…In this first-in-human proof-ofmechanism study, Tarish and colleagues demonstrated longitudinally that castration primarily affected both Ku and DNAPKcs expression in response to radiotherapy, leading to significant impairment of the nonhomologous end-joining (NHEJ) pathway of DSB (5). In parallel, Polkinghorn and colleagues and Goodwin and colleagues also observed a radiosensitization effect as a consequence of androgen blockade, and attributed this to the transcriptional downregulation of DNA repairrelated genes, with DNA-PKcs being a key target (6,7).…”
Section: 2mentioning
confidence: 93%